Outsourcing av vaskevannet - veien til likestilte praksiser? - Fjell, Tove Ingebjørg (Tidsskrift for kulturforskning, 2006)
In this article nine women and one man, a group of urban informants with higher education is interviewed on their domestic cleaning practices and on their reasons for hiring a private cleaner. The informants are in favour of equal sharing, their practices however are gender specific. It is a common finding among such couples that the non-equal is presented as equal, that the male partner’s contribution is exaggerated, and that the female partner’s contribution is understated. This particular study shows no evidence of this. One explanation is that the informants, by bringing in a third party (the cleaner), have effectively resolved the gender-defined conflict.